Fish gut-associated bacterial communities in a tropical lagoon (Aghien lagoon, Ivory Coast) - Gallet, Alison; Yao, Eric Kouamé; Foucault, Pierre; Bernard, Cécile; Quiblier, Catherine; Humbert, Jean-François; Coulibaly, Julien Kalpy; Troussellier, Marc; Marie, Benjamin; Duperron, Sébastien (Frontiers in Microbiology, 2022)
Lagoon Aghien (Ivory Coast) is a eutrophic freshwater lagoon that harbours high biomasses of phytoplankton. Despite Increasing interest in fish gut microbiomes diversity and functions, little data is currently available regarding will species from tropical west African lakes. Here, gut-associated bacterial communities are investigated in four fish species that are consumed by locale populations, namely the Cichlidae Hemichromis fasciatus, Tilapia guineensis and Sarotherodon melanotheron, and the Claroteidae Chrysichthys nigrodigitatus. Species-related differences are identified, that can be attributed to host phylogeny and diet. Important variations throughout the year are observed in T. guineensis and Chrysichthys nigrodigitatus, the two species that were sampled at all time points. This result emphasized the importance of time-series sampling and comparison with environmental variables even in tropical regions, that are not often conducted in wild populations. Effects of environmental factors (anthropogenic or not) on the microbiota and potential outcomes for fish health and populations sustainability need to be further explored. Interestingly, fish appear as major reservoirs of bacterial diversity, suggesting that they could contribute to the overall stability and resilience of bacterial communities present in the Lagoon Aghien.